Absorption cross section of ozone isotopologues calculated with the Multiconfiguration Time-Dependent Hartree (MCTDH) method: I. The hartley and huggins bands - Ndengué, Steve; Gatti, Fabien; Schinke, Reinhard; Meyer, Hans-Dieter; Jost, Rémy (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2010)
The absorption cross sections of 18 isotopologues of the ozone molecule have been calculated in the range of the Hartley−Huggins bands (27000−55000 cm−1). All 18 possible ozone isotopologues made with 16O, 17O, and 18O have been considered, with emphasis on those of geophysics interest like 16O3 17O16O2, 16O17O16O, 18O16O2, and 16O18O16O. We have used the MCTDH algorithm to propagate wavepackets. As an initial wavepacket, we took the vibrational ground state multiplied by the transition dipole moment surface. The cross sections have been obtained from the autocorrelation function of this wavepacket. Only two potential energy surfaces (PESs) and the corresponding transition dipole moment are involved in the calculation. The dissociating R state has been omitted. The calculations have been performed only for J = 0. The comparison with the experimental absorption cross sections of 16O3 and 18O3 has been performed after an empirical smoothing which mimics the rotational envelop. The isotopologue dependence of the cross sections of 18 isotopologues can be split into two energy ranges, (a) from 27000 to 32000 cm−1, the Huggins band, which is highly structured, and (b) from 32000 to 55000 cm−1, the main part of the cross section which has a bell shape, the Hartley band. This bell-shaped envelop has been characterized by a new analytic model depending on only four parameters, amplitude, center, width, and asymmetry. The isotopologue dependence of these parameters reveals the tiny differences between the absorption cross sections of the various isotopologues. In contrast to the smooth shape of the Hartley band, the Huggins band exhibits pronounced vibrational structures and therefore shows large isotopologue differences which may induce a significant isotopologue dependence of the ozone photodissociation rates under actinic flux.
Gesehen am 08.05.2023